2019
DOI: 10.1016/j.ebiom.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/CDK6 inhibition as a novel strategy to suppress the growth and survival of BCR-ABL1T315I+ clones in TKI-resistant CML

Abstract: Ponatinib is the only approved tyrosine kinase inhibitor (TKI) suppressing BCR-ABL1 T315I-mutated cells in chronic myeloid leukemia (CML). However, due to side effects and resistance, BCR-ABL1 T315I-mutated CML remains a clinical challenge. Hydroxyurea (HU) has been used for cytoreduction in CML for decades. We found that HU suppresses or even eliminates BCR-ABL1 T315I + sub-clones in heavily pretreated CML patients. Based on this observation, we investigated the effects of HU on TKI-resistant CML cells in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 61 publications
(92 reference statements)
1
24
0
Order By: Relevance
“…These results indicate that TCF7 may play a vital role in the development of drug resistance in chronic myeloid leukemia (CML) cells. An increasing number of studies have shown that replacing or combining other targets to conquer leukemia drug resistance has become a feasible strategy ( 48 , 49 ). In the present study, even when BCR-ABL1 activity was inhibited entirely, TCF7 expression was not significantly altered, indicating that TCF7 expression is BCR-ABL1-independent and combined targets of TCF7 and BCR-ABL1 may have a synergistic effect on the inhibition of CML imatinib-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that TCF7 may play a vital role in the development of drug resistance in chronic myeloid leukemia (CML) cells. An increasing number of studies have shown that replacing or combining other targets to conquer leukemia drug resistance has become a feasible strategy ( 48 , 49 ). In the present study, even when BCR-ABL1 activity was inhibited entirely, TCF7 expression was not significantly altered, indicating that TCF7 expression is BCR-ABL1-independent and combined targets of TCF7 and BCR-ABL1 may have a synergistic effect on the inhibition of CML imatinib-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in vitro testing revealed great efficacy of palbociclib and ribociclib at concentrations readily achievable in the clinical setting. Moreover, synergistic effects of ponatinib in combination with HU or ciclibs against cells carrying highly resistant CMs including the T315I mutation have been demonstrated 16 . It appears therefore that the upregulation of CDK6 documented in BCR‐ABL1‐positive cells displaying the T315I mutation alone or as part of a CM, provides a therapeutically exploitable vulnerability of the mutant cells.…”
Section: Targeting Specific Bcr‐abl1 Mutant Subclones By Alternative mentioning
confidence: 99%
“…To achieve these goals, we compared two cellular systems that show very high (NB4 APL cells) or very low (K562 CML cells) sensitivity to hydroxyurea-induced apoptosis [11]. We incubated them with a clinically achievable dose of 0.5 mM hydroxyurea [7] for 24 h and analyzed cell lysates by mass spectrometry (Figure 1a). Proteomics showed that hydroxyurea decreased the levels of RAF1 in NB4 cells but not in K562 cells (Figure 1a, Supplementary Figure S1a).…”
Section: Global Identification Of Factors That Control Apoptosis In Response To Replication Stressmentioning
confidence: 99%
“…Chemotherapeutics eliminate transformed cells through the induction of replication stress and DNA damage [1][2][3]. Hydroxyurea is used as cytoreductive therapy for leukemic disorders and brain tumors [4][5][6][7]. This drug specifically inhibits ribonucleotide reductase (RNR) and thereby depletes the cellular dNTP pool [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation